Assessment of Comorbidity as a Risk Factor for Edematous Pancreatitis Considering IL-4 (C-590T) Gene Polymorphism - Serge Ivanovich Ivashchuk; Larysa Petrivna Sydorchuk (Galician Medical Journal, 2017)
The comorbidities affect the course of pancreatitis significantly; however, this effect has not been evaluated from the perspective of genetic component. The objective of the research was to analyse concomitant chronic diseases as potential risk factors for edematous pancreatitis considering genetic predictors. Materials and methods. The epidemiological analysis of comorbidities (cholelithiasis, urolithiasis, ischemic heart disease, past viral infection) as risk factors for edematous pancreatitis was performed. Polymorphic variants of the IL-4 (rs 2243250) gene being identified in 123 patients and 40 healthy individuals were also involved. Results. In patients with edematous pancreatitis, urolithiasis was observed more frequently than in the control group - by 37.30% (χ2=18.62, p<0.001). The presence of cholelithiasis insignificantly increases the risk of edematous pancreatitis in the future (RR-1.156; 95% CI: 0.972-1.374). The presence of urolithiasis increased the risk of edematous pancreatitis twofold (RR-2.039; 95% CI: 1.346-3.090; p<0.05). Conclusions. 1. Cholelithiasis increases the probability of developing edematous pancreatitis in carriers of the mutant T-allele of the IL-4 gene by 3.7 times (RR=3.69; OR=10.13; 95% CI OR: 3.17-32.42; p<0.05). 2. In the C-allele carriers of the IL-4 (C-590T) gene, the risk of developing acute pancreatitis is twice higher in the presence of urolithiasis or ischemic heart disease, and almost five times higher in case of past viral infection (p<0.05).